(untitled) (PANGEEA, 2025)
Development of road infrastructure together with the rising number of cars has led to an increase in the number of asphalt plants. Asphalt is made of different types of mineral aggregates and bitumen, the latter being obtained from petroleum refineries residues. As they are not combustion emissions, air emissions generated by asphalt paving are usually neglected, being not considered major sources of emission. Miscellaneous research studies conducted in the last years have shown that this type of emissions is quite significant, as it continues to exist long after the road was paved, with increased values during hot weather. This study estimated the emissions resulted from the pavement of a street located in Alba Iulia city, Romania, from asphalt production to road paving and even after construction works were finished. The study was conducted using the emission estimation methods approved in Romania. Also, the research covered the emissions resulted from aggregates storage and those coming from the exhausting pipes of the equipment operated inside the asphalt plant.